Typical Cases Of Liver And Lung Hydatidosis In Murrah Buffaloes From Punjab (India) (Applied Biological Research, 2012)
Hydatidosis is one of the important zoonotic diseases caused by larval stages of Echinococcus  granulosus with economic implications in terms of reduction in livestock production due to  condemnation of infected organs of slaughtered animals (Umur and Kaaden, 2003). Buffaloes act as  one of the intermediate hosts of parasite harbouring hydatid cyst mainly in organs like liver and lungs  and has also been reported from several parts of India (Dhote et al., 1992; Sharma et al., 2000). The  present communication reports hydatid cysts in Murrah buffaloes from Punjab (India).
Keywords: Hydatidosis; India; Buffaloes